Simple harmonic motion studied on spring-mass system using Phyphox application - Infianto Boimau; Landiana E. Laos (Universitas Ahmad Dahlan, 2024)
Simple harmonic motion experiments have been conducted using a smartphone-based spring-mass system with the Phyphox application. This research aims to investigate the relationship between the mass of an object and the period and frequency of oscillations and determine the spring constant using smartphone-based experimental equipment. The method uses the "spring" feature in the Phyphox application to visualize oscillatory movements in real-time and measure the period and frequency of oscillations. The experimental results show that the spring constant obtained from the smartphone-based experiment is 9.51 N/m, with a difference of 1.25% compared to the Hooke's Law experimental setup with the conventional method. This shows that using a smartphone-based experimental setup can be a better alternative for conducting physics experiments requiring high accuracy.